(untitled) (Південний архів (історичні науки), 2025)
The article examines the changes in the healthcare system of Kirovohrad (now Kropyvnytskyi) during the German occupation of 1941–1944. The relevance of this study is determined by the insufficient scholarly coverage of the functioning of medical institutions and public healthcare under occupation, which is crucial for understanding the history of medicine and social policy in extreme conditions. Purpose: The purpose of the article is to analyze the condition, organization, and functioning of the healthcare system in Kirovohrad during the Nazi occupation, to describe the specific work of medical institutions, population access to medical services, and the impact of war on the epidemiological situation. Research Methods: A systematic approach was applied to analyze official documents and periodicals of the time, which enabled a comprehensive study of the functioning of the healthcare system under occupation, taking into account the influence of social, economic, and political factors on medical institutions. The comparative-historical method was used to establish the state of healthcare before and during the occupation, which allowed for tracing the dynamics of changes and their consequences for the population. The interdisciplinary approach (history, sociology, history of medicine) expanded the analytical framework of the study and provided a deeper insight into the social aspects of healthcare under wartime occupation. Research Results: The study established that during the occupation, a significant portion of medical institutions was repurposed to serve the German military, which significantly limited civilians’ access to medical care. By 1942, only a limited number of doctors remained in the city, strictly controlled by the occupation authorities. The article documents outbreaks of typhus, malaria, and other diseases caused by deteriorated sanitary and epidemiological conditions, lack of medicines, and absence of vaccines. A system of paid medical services and "hospital funds" for employed individuals was introduced to provide a minimal level of healthcare, yet even these mechanisms could not meet the medical needs of the population. Special attention is given to the issue of underground medical assistance provided by local doctors at the risk of persecution. Conclusions: The study demonstrates that Kirovohrad’s healthcare system during the occupation was disorganized and subordinated to the interests of the occupying authorities. The main problems included destroyed infrastructure, a shortage of qualified personnel, medicines, and preventive means. According to the author, the actions of local medical personnel were a form of social resistance and humanitarian responsibility. The analysis shows that the German administration viewed healthcare not as a tool to protect civilians but as a means of maintaining the working capacity of a population needed for the economy. The findings indicate that the medical system in Kirovohrad under occupation fulfilled only limited functions in providing assistance, reflecting the deliberate policy of the occupation authorities to restrict civilian access to healthcare.